2011
DOI: 10.1179/030192310x12706364542588
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ti inclusions in wire cord steel

Abstract: Ti content in specimens of 80 grade wire cord steel was measured by laser ablation inductively coupled plasma mass spectrometry. It was found that the average Ti content increased and then decreased during electrical arc furnace (EAF) tappingRrefiningRcontinuous casting. Under current control condition of 80 grade wire cord steel in Nanjing Iron and Steel United Co. Ltd (NISUCL), the calculation results in several aspects such as formation thermodynamics, solidification segregation and growth kinetics of TiN p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Cai et al [9] showed that the precipitation of TiN could only occur in the solid-liquid two-phase region where the solid fraction was greater than 0.95, and the particle size of TiN decreased with increasing cooling rate. Similar results were also reported in other references [11][12][13]. However, Liu et al [14] demonstrated that TiN would not precipitate in the liquid phase or mushy zone, but in austenite (γ-Fe).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Cai et al [9] showed that the precipitation of TiN could only occur in the solid-liquid two-phase region where the solid fraction was greater than 0.95, and the particle size of TiN decreased with increasing cooling rate. Similar results were also reported in other references [11][12][13]. However, Liu et al [14] demonstrated that TiN would not precipitate in the liquid phase or mushy zone, but in austenite (γ-Fe).…”
Section: Introductionsupporting
confidence: 88%
“…where a TiN , a [Ti] , and a [N] denote the activities of TiN, Ti, and N in molten steel, respectively, herein, a TiN = 1; w [Ti] and w [N] denote the mass fractions of Ti and N in molten steel, respectively; f [Ti] and f [N] denote the activity coefficients of Ti and N, which can be estimated by Equations (10) and (11) [13], respectively.…”
Section: Materials and Equilibrium Solubility Productmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships for the activity coefficients of Ti and N (f Ti and f N , respectively) as a function of temperature are given by Eqs. [9] and [10]: [34][35][36] lg f i 1873 K 1600 C are obtained. Substituting these values into Eqs.…”
Section: Thermodynamics Of Tin Formationmentioning
confidence: 99%
“…Titanium is always used as a kind of stabilizing element, which reacts with the carbon or nitrogen to form carbonitride to bind the soluble carbon and nitrogen, especially for IF steels, 1) Ti-bearing stainless steels 2) or wire cord steels. 3) In addition, Ti-oxide in steel can be nucleating sites for intragranular acicular ferrite during solidification, and improve mechanical properties around welded region in steels. [4][5][6][7][8] However, Ti-containing inclusions may also cause severe nozzle clogging problems, which are detrimental to steel production process.…”
Section: Introductionmentioning
confidence: 99%